Characterization of ZnO:Sn Nanopowders Synthesized by Co-precipitation Method - Prasopporn Junlabhut; Wanichaya Mekprasart; Russameeruk Noonuruk; Krisana Chongsri; Wisanu Pecharapa (My University, 2014)
ZnO:Sn nanopowders were synthesized by co-precipitation method using zinc acetate dihydrate and tin (IV) chloride hexahydrate as a precursors. Co-precipitate of ZnO:Sn nanopowders with various Sn additive 0-50%wt were obtained by calcination process at 500 ̊C. The corresponding functional groups and chemical bonding of the samples were investigated by Fourier Transform Infrared Spectroscopy (FTIR). The effects of Sn addition on structural and morphological properties of ZnO:Sn nanopowders have been investigated by X-ray diffraction (XRD), Raman Spectroscopy (Raman) and Scanning electron microscopy (SEM). The chemical bonding of Zn-O, Sn-O and Sn-OH in ZnO:Sn nanopowders were observed by FTIR results. The phase formation of this coumpound was observed with increasing Sn content with calcined at 500 ̊C. These results indicate that the crystallinity and structural of ZnO nanopowders are significantly affected by Sn dopant.
Keywords: Coprecipitation; ZnO doping and properties